Randomized Clinical Trial of Vitamin D3 Doses on Prostatic Vitamin D Metabolite Levels and Ki67 Labeling in Prostate Cancer Patients - Wagner, Dennis; Trudel, Dominique; Van der Kwast, Theodorus; Nonn, Larisa; Giangreco, Angeline Antonio; Li, Doris; Dias, Andre; Cardoza, Monique; Laszlo, Sanda; Hersey, Karen; Klotz, Laurence; Finelli, Antonio; et al. (The journal of clinical endocrinology and metabolism, 2013)
Context:Vitamin D3 might benefit prostate cancer (PCa) patients because prostate cells can locally synthesize the active hormone calcitriol.Objective:Our objective was to determine the effects of oral vitamin D3 on vitamin D metabolites and PCa proliferative activity in prostate tissue.Design and Setting:We conducted a double-blind randomized clinical trial at surgical oncology clinics in Toronto, Canada.Patients:PCa patients (Gleason 6 or 7) participated in the study. Of 66 subjects who were enrolled, 63 completed the dosing protocol.Intervention:Vitamin D3 (400, 10 000, or 40 000 IU/d) was orally administered before radical prostatectomy.Main Outcome Measures:We evaluated vitamin D metabolite levels and Ki67 labeling in surgical prostate tissue. Safety measures, PTH, and prostate-specific antigen (PSA) were also assessed.Results:Prostate tissue and serum levels of vitamin D metabolites, including calcitriol, increased dose dependently (P < .03) and were significantly higher in the 40 000-IU/d group than in every other dose group (P < .03). Prostate vitamin D metabolites correlated positively with serum levels (P < .0001). Ki67 measures did not differ significantly among vitamin D dose groups. However, cross-sectional analysis indicated that the calcitriol level attained in prostate was inversely associated with Ki67 intensity and Ki67 (3+) percent positive nuclei in PCa and benign tissue (P < .05). Safety measures did not change adversely with dosing. Compared with the 400-IU/d group, serum PTH and PSA were lower in the combined higher-dose groups at the end of the study (P < .02).Conclusions:Oral vitamin D3 raised prostate calcitriol levels (level 1 evidence) and modestly lowered both PSA and PTH. Although Ki67 expression did not differ among dose groups, its levels correlated inversely with prostate calcitriol. These suggestions of clinical benefit justify continued clinical research.